An energy conversion / storage system based on high electrical / thermal conductivity ultra-high performance concrete and its application

By using molybdenum chromium stainless steel microwires and stainless steel mesh electrodes in high-performance concrete, the problems of insufficient conductivity and heat transfer performance and poor mechanical properties in the prior art are solved, and an efficient and stable energy conversion and storage system is achieved.

CN115748350BActive Publication Date: 2025-03-07DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211466428.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-03-07
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

Existing high-performance concrete cannot improve the conductivity and heat transfer properties under low dosage. High-volume conductive fillers will affect the mechanical properties, and the conductive fillers are prone to rust, affecting the long-term stability and efficiency of the system.

Method used

Molybdenum chromium stainless steel microwires are used as conductive and heat transfer components, combined with stainless steel mesh electrodes to prepare high-conductive/thermal conductivity ultra-high performance concrete to form a widely distributed overlap network, improve the conductive and heat transfer properties of concrete, and simplify the production process through conventional preparation processes.

Benefits of technology

It significantly improves the stability and efficiency of the conductivity and heat transfer properties of concrete, enhances mechanical properties, reduces production costs, and maintains long-term stability in complex environments. It is suitable for a variety of energy conversion and storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE006
    Figure DEST_PATH_IMAGE006
Patent Text Reader

Abstract

The present invention discloses an energy conversion / storage system based on high-conductivity / thermal-conductivity ultra-high-performance concrete and its application, which belongs to the field of intelligent / multifunctional cement-based material preparation and application. The present invention uses molybdenum-chromium stainless steel microwires with micron-level diameter, excellent electrical and thermal conductivity, high mechanical and stainless properties and ultra-high-performance concrete to synergistically prepare high-conductivity / thermal-conductivity ultra-high-performance concrete, and then develops an energy conversion / storage system based on the high-performance concrete with high conversion / storage efficiency, good long-term stability, excellent mechanical properties, and meeting the requirements of small-section / thin-plate component size. It can be directly used to develop bridge panels, road panels, airport road panels, steps and tunnel entrances that melt snow and ice through electric heating, for farms and household floor heating that use electric heating for heating, for bridge panels, road panels and airport road panels that collect thermoelectric energy by themselves; it can also be used as a solar thermal storage module to improve the collection and utilization rate of new energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an energy conversion / storage system based on highly conductive / thermally conductive ultra-high performance concrete and its application, belonging to the field of preparation and application of intelligent / multifunctional cement-based materials and the field of green energy and new energy technology. Background Art

[0002] The core of developing high-performance energy conversion / storage systems based on conductive concrete is to give concrete excellent and long-term stable electrical and thermal conductivity and ensure its high strength, high toughness and high durability. In existing studies, carbon-based conductive fillers are often used to improve the electrical conductivity and thermal transfer performance of concrete, mainly including carbon fiber, carbon nanotubes, carbon nanofibers, graphene, etc. However, these carbon-based conductive fillers have poor compatibility with concrete and require specific dispersion technology or the addition of dispersants, which makes the preparation process complicated and the production cost increased; at the same time, low-dosage carbon-based conductive fillers cannot give concrete high electrical conductivity, while high-dosage carbon-based conductive fillers are easy to agglomerate and introduce a large number of macroscopic defects in concrete, which has an adverse effect on its mechanical properties; in addition, the high porosity of ordinary concrete makes its electrical conductivity and thermal transfer performance easily affected by the ambient temperature and humidity, which in turn affects the stability and efficiency of the energy conversion / storage system prepared by it, and the strength and toughness of ordinary concrete are insufficient, making the energy conversion / storage system components prepared by it large and heavy. Due to its dense microstructure, high strength, high toughness and high durability, ultra-high performance concrete has been widely used in important structures such as long-span bridges, super-high-rise buildings and nuclear engineering facilities. It can significantly reduce the size of components with the same bearing capacity and can be used to develop slender and thin plate components and their structures. Therefore, the development of ultra-high performance concrete with high electrical conductivity and thermal conductivity is expected to meet the high stability and durability required by concrete for energy conversion / storage systems. However, the commonly used conductive filler in ultra-high performance concrete in the past is steel fiber with a diameter of 0.12-0.30mm, which cannot improve the electrical conductivity and heat transfer performance of ultra-high performance concrete at low dosage, while high dosage of steel fiber will have an adverse effect on the workability of ultra-high performance concrete, thereby affecting the density, strength and durability of its hardened structure. In addition, the commonly used steel fibers in previous studies are prone to rust in complex service environments, thereby affecting the stability of the electrical conductivity and heat transfer performance of ultra-high performance concrete, and the efficiency and long-term performance of the energy conversion / storage system prepared by it. This means that the energy conversion / storage system developed based on ordinary steel fiber ultra-high performance concrete has low efficiency and poor long-term stability, and the voltage required to prepare the electrothermal conversion system is large and the operation safety is poor. It should also be noted that copper plates or stainless steel plates are often used as collecting electrodes for electrothermal / thermoelectric energy conversion in previous studies, but there is a weak interface between the electrode and the concrete matrix, which is not conducive to maintaining the integrity of the component. Summary of the invention

[0003] To solve the above problems, the purpose of the present invention is to provide an energy conversion / storage system based on high electrical / thermal conductivity ultra-high performance concrete with high conversion / storage efficiency, good long-term stability, excellent mechanical properties, simple production process and wide application range.

[0004] Technical solution:

[0005] An energy conversion / storage system based on highly conductive / thermally conductive ultra-high performance concrete, which, when used as an electrothermal / thermoelectric energy conversion system, consists of highly conductive / thermally conductive ultra-high performance concrete and embedded electrodes; when used as an energy storage system, consists of highly conductive / thermally conductive ultra-high performance concrete, a heat-conducting fluid and an insulation layer.

[0006] Furthermore, in the above technical solution, when used as an electrothermal / thermoelectric energy conversion system, the embedded electrode inside the high electrical / thermal conductivity ultra-high performance concrete adopts a mesh size of 2-5 mm 2 The area of ​​each electrode is slightly smaller than the cross-sectional area of ​​the system, and the positive and negative electrodes are 5-10 mm away from the edge of each system. When used as an energy storage system, the heat transfer fluid poured into the high electrical conductivity / thermal conductivity ultra-high performance concrete can be water, molten salt or heat transfer oil, and the external insulation layer material can be foam concrete, expanded clay or pumice lightweight aggregate concrete.

[0007] Stainless steel mesh two electrodes refer to the use of a two-electrode method to set up a stainless steel mesh electrode, in which two stainless steel meshes are pre-embedded as electrodes in a high electrical / thermal conductivity ultra-high performance concrete matrix.

[0008] During the preparation of the energy storage system, pipes are pre-buried inside a highly conductive / thermally conductive ultra-high performance concrete matrix, and heat transfer fluid is poured through the pre-buried pipes.

[0009] Furthermore, in the above technical solution, the highly conductive / thermal conductive ultra-high performance concrete is prepared by adding stainless steel microwires as thermoelectric components to an ultra-high performance concrete matrix; the stainless steel microwires are made of molybdenum-chromium stainless steel with excellent corrosion resistance, have a diameter of 5 to 30 μm, a length of 5 to 15 mm, an elongation of more than 1%, a tensile strength of more than 780 MPa, and an admixture of 15% to 40% of the cement mass.

[0010] The high electrical / thermal conductivity ultra-high performance concrete has a compressive strength greater than 120 MPa, a flexural strength greater than 15 MPa, a thermal conductivity greater than 1.5 W / (m×K), a specific heat capacity greater than 0.85 kJ / (kg×K), and is made through conventional preparation and curing processes.

[0011] Specifically, the high electrical / thermal conductivity ultra-high performance concrete includes cement, fly ash, silica fume, quartz sand, molybdenum-chromium stainless steel microwires, water and a water reducing agent.

[0012] Specifically, the high electrical / thermal conductivity ultra-high performance concrete is obtained by mixing the following raw materials in weight ratio according to a conventional method:

[0013] Cement: fly ash: silica ash: quartz sand: molybdenum-chromium stainless steel microwire: water: water reducing agent = 1: 0.20~0.40: 0.20~0.40: 1.0~1.5: 0.15~0.40: 0.30~0.40: 0.005~0.035.

[0014] The particle size of the silica fume is 0.1-0.3 µm; the particle size of the quartz sand is 0.12-0.80 µm; the fly ash is Class I fly ash; and the water reducing agent is a polycarboxylic acid-based water reducing agent, with a water reducing rate greater than 30%.

[0015] The present invention provides the application of the above-mentioned energy conversion / storage system based on high electrical / thermal conductivity ultra-high performance concrete in bridge panels, road panels, airport road panels, steps and tunnel entrances that melt snow and ice through electric heating, and in farms and household floor heating that provide heating through electric heating.

[0016] The present invention provides the application of the energy conversion / storage system based on highly conductive / thermally conductive ultra-high performance concrete in bridge panels, road panels and airport road panels that realize energy self-collection by converting thermal energy into electrical energy.

[0017] The present invention provides application of the energy conversion / storage system based on high electrical / thermal conductivity ultra-high performance concrete in an energy thermal storage module.

[0018] The present invention uses molybdenum-chromium stainless steel microwires to improve the conductivity, heat transfer, strength and toughness of ultra-high performance concrete, and then develops an energy conversion / storage system with high conversion / storage efficiency, good long-term stability, excellent mechanical properties, simple production process and wide application range based on high conductivity / thermal conductivity ultra-high performance concrete. Its action mechanism mainly includes the following three aspects: ① Due to its micron-level diameter, large specific surface area, good heat transfer and electrical conductivity and high mechanical properties, the stainless steel microwires can form a widely distributed overlapping network in the ultra-high concrete matrix, significantly improving the conductivity and heat transfer performance of the concrete, and can effectively inhibit the generation and development of primary cracks, and can also cross and bridge cracks, thereby improving the strength, toughness and high temperature degradation resistance of the concrete; in addition, active ultra-fine powder is generally used in large quantities in ultra-high performance concrete, which can adhere to the surface of stainless steel microwires and continue to undergo secondary hydration, which makes it impossible for the stainless steel microwires to have a weak interface with the matrix, which is also conducive to the improvement of the strength and toughness of ultra-high performance concrete. ② Since the stainless steel microwires can form a complete conductive and heat transfer path inside the ultra-high performance concrete, this greatly improves the stability of its conductive and heat transfer performance. At the same time, molybdenum-chromium stainless steel microwires will not rust in a complex service environment for a long time, and the ultra-high performance concrete matrix has high density, high impermeability and high corrosion resistance, which makes the stainless steel microwire modified high conductivity / thermal conductivity ultra-high performance concrete have long-term and stable excellent performance. Its electrical and thermal conductivity is not easily affected by environmental temperature and humidity, energy conversion working times, etc., and can maintain stable performance during repeated energy conversion, storage and release. ③ Since the particle size of some aggregates used in ultra-high performance concrete is smaller than the aperture of stainless steel mesh electrodes, pre-embedded stainless steel mesh electrodes do not affect the overall performance of the specimen, nor do they have an adverse effect on its mechanical properties. Therefore, it is reasonable to pre-embed stainless steel mesh electrodes in stainless steel microwire ultra-high performance concrete to prepare an energy conversion system. ④ Due to the large thermal conductivity of stainless steel microwires, the incorporation of stainless steel microwire networks can give ultra-high performance concrete a high thermal conductivity; and based on the conduction of heat by stainless steel microwire networks and the restriction and overlap of microcracks, the incorporation of stainless steel microwires can improve the high temperature burst resistance and high and low temperature cycle resistance of ultra-high performance concrete. This allows stainless steel microfilament ultra-high performance concrete to be used as the core of a solar thermal energy storage module, and together with heat transfer fluid and external insulation materials, form a solar thermal storage system.

[0019] Beneficial effects of the invention: high-conductivity / thermal-conductivity ultra-high-performance concrete is prepared by adding molybdenum-chromium stainless steel microwires and adopting conventional processes, and then combined with the pre-buried electrode process to prepare an electrothermal energy conversion system, which can be directly used to develop bridge panels, road panels, airport road panels, steps and tunnel entrances that melt snow and ice through electric heating, and can be used in farms and home floor heating that use electric heating for heating. Its high conductivity can improve the electrothermal conversion efficiency and the rate of snow and ice melting, reduce the operating voltage, and improve the safety of operation. It can also separate the ice surface from the road surface through short-term heating and combine with mechanical snow shoveling under low energy consumption. It can be used to remove ice and melt snow to meet the needs of smooth traffic in cold areas in winter. It can also be used to prepare thermoelectric energy conversion systems based on high electrical conductivity / thermal conductivity ultra-high performance concrete and stainless steel mesh electrodes, and use them to develop thermoelectric self-collecting bridge panels, road panels and airport road panels. The temperature difference between the upper and lower layers of the components can be used to convert solar energy into electrical energy to power street lights, billboards, etc. or to store electrical energy, which is of great significance for energy conservation. It can also be used to prepare solar thermal storage modules by combining high electrical conductivity / thermal conductivity ultra-high performance concrete with heat-conducting fluids and thermal insulation materials, which is beneficial to improving the collection and utilization rate of new energy. DETAILED DESCRIPTION

[0020] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0021] The electrothermal energy conversion / storage system was prepared based on high-conductivity / thermal-conductivity ultra-high performance concrete and stainless steel mesh electrodes. The DC resistance of the two electrodes of the high-conductivity / thermal-conductivity ultra-high performance concrete was measured using a Keithley 2100 digital multimeter, and the results were calculated according to the formula Calculation can be done to obtain the resistivity r ,in R -resistance; S - cross-sectional area of ​​the specimen; L -The distance between the two electrodes. When preparing the electrothermal energy conversion system, the plate specimen used was 400 mm×100 mm×15 mm in size, and the stainless steel mesh electrodes were pre-buried inside the specimen with a spacing of 380 mm and a distance of 10 mm from the edges on both sides. In order to obtain the electrothermal energy conversion performance and efficiency of the system, a 30 V DC voltage was used to circulate the power to conduct a temperature rise test, and its resistivity was measured again before and after the temperature rise and snow melting and ice melting. When conducting the ice melting test, the ice layer thickness was 9 mm, the applied voltage was 30 V, and the test environment temperature was -25.0~-26.0℃; when conducting the snow melting test, the snow layer thickness was 5 cm of natural accumulation snow layer and 2 cm of artificial compacted snow layer, the applied voltage was 25 V, the test environment was an outdoor open field at about -5 ℃, and the wind speed could reach up to 5.36 m×s -1The law of conservation of energy is used to calculate the electric-heat conversion rate of snow-melting and ice-melting to characterize the efficiency of the system. When preparing the energy storage system, steel pipes are embedded in the rectangular specimen, and the two ends of the specimen are connected to the pressure pump for the input and output of the heat transfer oil. A foam concrete insulation layer is set on the outside of the specimen.

[0022] Example 1

[0023] This embodiment uses molybdenum-chromium stainless steel microwires to improve the conductivity, heat transfer, strength and toughness of ultra-high performance concrete, and then develops an electrothermal energy conversion / storage system with high conversion efficiency, good long-term stability, excellent mechanical properties, simple production process and wide application range based on high electrical / thermal conductivity ultra-high performance concrete and stainless steel mesh electrodes. The system is suitable for preparing bridge panels, road panels, airport road panels, steps and tunnel entrances that can melt snow and ice through electric heating, and can be used in farms and home floor heating that use electric heating for heating.

[0024] In this embodiment, the size of the high electrical / thermal conductivity ultra-high performance concrete specimen is The internal embedded electrode adopts a mesh size of 3 mm 2 The stainless steel mesh electrodes each have an area of , the positive and negative electrodes are 10 mm away from the edge of the length of the specimen. In this embodiment, the high electrical conductivity / thermal conductivity ultra-high performance concrete includes cement: fly ash: silica fume: quartz sand: stainless steel microwire: water: water reducer = 1:0.25:0.31:1.37:0.16:0.38:0.015 by weight. The cement grade is 42.5R; the fly ash is Class I fly ash; the particle size of silica fume is 0.1-0.3 µm; the particle size of quartz sand is 0.12-0.80 µm, and the SiO 2 The content is ≥99%; the material of the stainless steel microwire is molybdenum-chromium stainless steel, with a diameter of 20 μm, a length of 10 mm, an elongation of >1%, and a tensile strength of greater than 780 MPa; the water reducer is a polycarboxylic acid-based water reducer, which is prepared by a conventional mixing process, and the mixed high-conductivity / thermal-conductivity ultra-high-performance concrete is poured into a test mold, and then it is demolded after being cured in a standard curing box (temperature 20±1°C, humidity ≥95%) for 24 hours, and then the specimen is placed in 20±1°C water for curing for 28 days and then placed in the air for 72 days for testing.

[0025] Example 2

[0026] The present embodiment adopts molybdenum-chromium stainless steel microwires to improve the electrical conductivity, heat transfer, strength and toughness of ultra-high performance concrete, and then develops an electrothermal energy conversion system based on high electrical / thermal conductivity ultra-high performance concrete and stainless steel mesh electrodes, which has high conversion efficiency, good long-term stability, excellent mechanical properties, simple production process and wide application range. The system is suitable for preparing bridge panels, road panels, airport road panels, steps and tunnel entrances that can melt snow and ice through electric heating, and can be used in farms and home floor heating that use electric heating for heating.

[0027] In this embodiment, the size of the high electrical / thermal conductivity ultra-high performance concrete specimen is The internal embedded electrode adopts a mesh size of 3 mm 2 The stainless steel mesh electrodes each have an area of , the positive and negative electrodes are 10 mm away from the edge of the specimen length. In this embodiment, the high electrical / thermal conductivity ultra-high performance concrete includes cement: fly ash: silica fume: quartz sand: stainless steel microwire: water: water reducer = 1:0.25:0.31:1.37:0.20:0.38:0.015 by weight. The cement grade is 42.5R; the fly ash is Class I fly ash; the particle size of silica fume is 0.1-0.3 µm; the particle size of quartz sand is 0.12-0.80 µm, and the SiO 2 Content ≥99%; the material of the stainless steel microwire is molybdenum-chromium stainless steel, with a diameter of 20 μm, a length of 10 mm, an elongation of >1%, and a tensile strength of greater than 780 MPa; the water reducer is a polycarboxylic acid water reducer. It is made by conventional mixing process, the stirred high-conductivity / thermal-conductivity ultra-high-performance concrete is poured into the test mold, and then it is demolded after curing in a standard curing box (temperature 20±1℃, humidity ≥95%) for 24 hours, and then the specimen is placed in 20±1℃ water for 28 days and then placed in the air for 72 days for testing.

[0028] Example 3

[0029] In this embodiment, the size of the high electrical / thermal conductivity ultra-high performance concrete specimen is The internal embedded electrode adopts a mesh size of 3 mm 2 The stainless steel mesh electrodes each have an area of , the positive and negative electrodes are 10 mm away from the edge of the length of the specimen. In this embodiment, the high electrical conductivity / thermal conductivity ultra-high performance concrete includes cement: fly ash: silica fume: quartz sand: stainless steel microwire: water: water reducer = 1:0.25:0.31:1.37:0.40:0.38:0.015 by weight. The cement grade is 42.5R; the fly ash is Class I fly ash; the particle size of silica fume is 0.1-0.3 µm; the particle size of quartz sand is 0.12-0.80 µm, and the SiO 2Content ≥99%; the material of the stainless steel microwire is molybdenum-chromium stainless steel, with a diameter of 20 μm, a length of 10 mm, an elongation of >1%, and a tensile strength of greater than 780 MPa; the water reducer is a polycarboxylic acid water reducer. It is made by conventional mixing process, the stirred high-conductivity / thermal-conductivity ultra-high-performance concrete is poured into the test mold, and then it is demolded after curing in a standard curing box (temperature 20±1℃, humidity ≥95%) for 24 hours, and then the specimen is placed in 20±1℃ water for 28 days and then placed in the air for 72 days for testing.

[0030] Example 4

[0031] This embodiment uses molybdenum-chromium stainless steel microwires to improve the heat transfer, strength, toughness and high-temperature burst resistance of ultra-high performance concrete, and then develops an energy storage system with high conversion efficiency and good long-term stability based on high thermal conductivity ultra-high performance concrete and thermal insulation concrete. It is suitable for preparing solar thermal storage modules and plays a role in utilizing renewable energy to absorb intermittent renewable energy.

[0032] In this embodiment, the size of the high thermal conductivity ultra-high performance concrete specimen is , the outer diameter of the two steel pipes embedded inside is 25mm, the inner diameter is 21mm, and the length is 800mm. The center lines of the cross sections of the two steel pipes are aligned with the center lines of the cross sections of the specimens, the upper and lower spacing is 30mm, and the distances from the upper and lower edges of the cross sections are 35mm. In this embodiment, the high thermal conductivity ultra-high performance concrete includes cement: fly ash: silica ash: quartz sand: stainless steel microfilaments: water: water reducing agent = 1:0.25:0.31:1.37:0.40:0.38:0.015 by weight. The cement grade is 42.5R; the fly ash is Class I fly ash; the particle size of silica ash is 0.1-0.3 µm; the particle size of quartz sand is 0.12-0.80 µm, SiO 2 Content ≥99%; the material of stainless steel microwire is molybdenum-chromium stainless steel, with a diameter of 20 μm, a length of 10 mm, an elongation of >1%, and a tensile strength of more than 780 MPa; the water reducer is a polycarboxylic acid water reducer. It is made by conventional mixing process, and the stirred high-conductivity / thermal-conductivity ultra-high-performance concrete is poured into the test mold (the test mold is pre-placed with a steel pipe), and then it is demolded after curing in a standard curing box (temperature 20±1℃, humidity ≥95%) for 24 hours, and then the specimen is placed in 20±1℃ water for curing for 28 days. Temperature sensors are arranged on the surface of the cured high-conductivity ultra-high-performance concrete, and 2cm thick foam concrete is laid on the outer layer. After the strength of the foam concrete develops for 7d, a heat storage test is carried out. The thermal fluid used in the embedded steel pipe is heat transfer oil.

[0033] Comparative Example 1

[0034] Comparative Example 1: Conductive concrete for road deicing was prepared using carbon fiber as the conductive phase. The specimen size was A plate-type component with two L-shaped copper mesh electrodes buried on both sides of the bottom of the plate.

[0035] In this comparative example, the carbon fiber conductive concrete includes cement: fly ash: sand: carbon fiber: water = 1: 0.32: 3.28: 0.75: 1.67 by volume, the mass of the water reducer added is 1.5% of the mass of all the mixtures, and 0.4% of the mass of the fiber dispersant is added. The cement is type I / II Portland cement produced by Holcim, which meets the ASTM-C-150 standard of the United States; the fly ash is class F fly ash with an average particle size of 19.5 mm; the sand is natural sand, which meets the ASTM-C-33 standard of the United States; the diameter of the chopped carbon fiber is 7.2 mm, the nominal length is 6 mm, the carbon content is 95%, and the resistivity is 1.55×10 -3 Ω·cm; the water reducer in this comparative example is a high-efficiency water reducer, and the fiber dispersant is fine powder methyl cellulose. Various materials for preparing carbon fiber conductive concrete are fully stirred in a drum stirring pot, and then the mixture slurry is poured into a mold for curing for 1 day, and after demolding, it is cured in a humid curing room at 23 °C for 7 days.

[0036] Comparative Example 2

[0037] Comparative Example 2: Conductive concrete was prepared by adding 1.5% steel fiber and 25% graphite powder by volume, and the conductive concrete was used to pave the road for outdoor snow melting. The size of each plate component was 560 cm × 200 cm × 9 cm, with a total of 18 plates. A 6 mm thick insulation layer was set under the conductive concrete pavement to reduce heat loss, and a slope of 15° (i.e. i =7.5%) to allow the melted snow water to flow away in time.

[0038] Performance Testing

[0039] The DC resistivity, temperature rise rate under different voltages, energy conversion rate, snow melting time, and ice thawing time of the thermoelectric conversion system based on high-conductive / thermal-conductive ultra-high-performance concrete and stainless steel mesh electrodes under different environments are shown in Table 1. Table 1 shows that with the increase in the amount of stainless steel microwires, the resistivity of ultra-high-performance concrete decreases, and the average temperature rise rate increases significantly. After multiple electrothermal temperature rises, snow melting and ice thawing processes, the DC resistivity of high-conductive / thermal-conductive ultra-high-performance concrete does not change, indicating that it has good electrical conductivity stability and electrothermal stability. Compared with carbon fiber, ordinary steel fiber and graphite powder, the use of stainless steel microwires improves the snow melting and ice thawing rate and energy utilization rate of ultra-high-performance concrete. In addition, the concrete prepared with carbon fiber, ordinary steel fiber and graphite powder does not have a dense microstructure and has poor electrical performance stability, resulting in its snow melting and ice thawing efficiency decreasing with the extension of service time. In addition, due to the large resistivity value of concrete prepared with carbon fiber, ordinary steel fiber and graphite powder, the voltage required to be applied when used for snow melting and ice thawing is high (up to more than 101 V), which reduces its operational safety.

[0040] Table 1 Effect of thermoelectric conversion system based on high electrical / thermal conductivity ultra-high performance concrete and stainless steel mesh electrodes

[0041]

[0042] In Example 4, the concrete module is preheated to 250°C before use, the inlet temperature of the heat transfer oil is 390°C when charging, and after 4 hours of charging, the temperature monitored inside the concrete specimen is 360°C, and the outlet temperature of the heat transfer oil is lower than 320°C when charging; the internal temperature of the concrete specimen is 350°C at the beginning of heat release, and the inlet temperature of the heat transfer oil during heat release is 290°C. After 1 hour of heat release, the internal temperature of the concrete specimen is 310°C, and the outlet temperature of the heat transfer oil is 330°C. The heat storage capacity utilization factor is calculated to be 42%, and the energy storage system has a high energy heat storage efficiency.

Claims

1. An energy conversion system based on high electrical / thermal conductivity ultra-high performance concrete, characterized in that: It is obtained by pre-embedding electrodes in high electrical / thermal conductivity ultra-high performance concrete, wherein the electrodes have a mesh size of 2-5 mm. 2 Two stainless steel mesh electrodes; The high electrical / thermal conductivity ultra-high performance concrete comprises cement, fly ash, silica fume, quartz sand, molybdenum-chromium stainless steel microwires, water and a water reducing agent; The weight ratio of cement: fly ash: silica fume: quartz sand: molybdenum-chromium stainless steel microwire: water: water reducing agent is 1: 0.20-0.40: 0.20-0.40: 1.0-1.5: 0.2-0.40: 0.30-0.40: 0.005-0.035; The molybdenum-chromium stainless steel microwire has a diameter of 5 to 30 μm, a length of 5 to 15 mm, an elongation greater than 1%, and a tensile strength greater than 780 MPa.

2. The energy conversion system based on high electrical / thermal conductivity ultra-high performance concrete according to claim 1 is characterized in that: The positive and negative electrodes of the two stainless steel mesh electrodes are 5-10 mm away from the edges of their respective systems.

3. The energy conversion system according to claim 1, characterized in that: The high electrical / thermal conductivity ultra-high performance concrete has a compressive strength greater than 120 MPa, a flexural strength greater than 15 MPa, a thermal conductivity greater than 1.5 W / (m·K), and a specific heat capacity greater than 0.85 kJ / (kg·K).

4. Application of the energy conversion system as claimed in claim 1 in bridge panels, road panels, airport road panels, steps and tunnel entrances that melt snow and ice through electric heating, or in farms and household floor heating that provide heating through electric heating.

5. Application of the energy conversion system according to claim 1 in a bridge deck, road deck or airport road deck that realizes energy self-collection by converting thermal energy into electrical energy.

6. The energy conversion system according to claim 1 is used in a solar thermal storage module.

7. An energy storage system based on high electrical / thermal conductivity ultra-high performance concrete, characterized in that: It includes high electrical / thermal conductivity ultra-high performance concrete, heat-conducting fluid inside the high electrical / thermal conductivity ultra-high performance concrete, and thermal insulation layer outside the high electrical / thermal conductivity ultra-high performance concrete; The high electrical / thermal conductivity ultra-high performance concrete comprises cement, fly ash, silica fume, quartz sand, molybdenum-chromium stainless steel microwires, water and a water reducing agent; The weight ratio of cement: fly ash: silica fume: quartz sand: molybdenum-chromium stainless steel microwire: water: water reducing agent is 1: 0.20-0.40: 0.20-0.40: 1.0-1.5: 0.2-0.40: 0.30-0.40: 0.005-0.035; The molybdenum-chromium stainless steel microwire has a diameter of 5 to 30 μm, a length of 5 to 15 mm, an elongation greater than 1%, and a tensile strength greater than 780 MPa.

8. An energy storage system based on high electrical / thermal conductivity ultra-high performance concrete according to claim 7, characterized in that: The heat transfer fluid is water, molten salt or heat transfer oil, and the insulation layer is made of foam concrete, ceramsite or pumice lightweight aggregate concrete material.

9. The energy storage system according to claim 7, characterized in that The high electrical / thermal conductivity ultra-high performance concrete has a compressive strength greater than 120 MPa, a flexural strength greater than 15 MPa, a thermal conductivity greater than 1.5 W / (m·K), and a specific heat capacity greater than 0.85 kJ / (kg·K).

10. Application of the energy storage system as claimed in claim 7 in bridge panels, road panels, airport road panels, steps and tunnel entrances that use electric heating to melt snow and ice, or in farms and household floor heating that use electric heating to provide heating.

11. Application of the energy storage system according to claim 7 in a bridge deck, a road deck or an airport road deck that realizes energy self-collection by converting thermal energy into electrical energy.

12. The energy storage system according to claim 7 is used in a solar thermal storage module.